ANALISIS STRATEGI PEMBELAJARAN IPA BERBASIS STEM UNTUK MENINGKATKAN KREATIVITAS DAN LITERASI SAINS SISWA - Maya Sih Hika Pamungkas (EL ROBIH: Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
This article aims to analyze STEM-based science learning strategies in enhancing students' creativity and scientific literacy. The research method used is a literature study by reviewing various recent national and international journal articles related to the application of STEM in science education. The results of the study indicate that STEM integration through learning models such as project-based learning and inquiry has proven effective in developing students' critical thinking skills, creativity, and scientific literacy skills. This strategy allows students to actively engage in solving real-life problems, generating innovative ideas, and understanding science concepts in a more in-depth and applicable manner. Thus, STEM-based learning can be a strategic alternative in facing the challenges of 21st-century education and is relevant for implementation at various levels of education.